The frozen elephant trunk technique for aortic dissection is safe after previous aortic repair. (10th October 2020) - Berger, Tim; Kreibich, Maximilian; Mueller, Felix; Rylski, Bartosz; Kondov, Stoyan; Schröfel, Holger; Pingpoh, Clarence; Beyersdorf, Friedhelm; Siepe, Matthias; Czerny, Martin
Abstract: OBJECTIVES: The goal of this study was to evaluate outcomes of aortic arch replacement using the frozen elephant trunk (FET) technique after previous proximal and/or distal open or endovascular thoracic aortic repair. METHODS: Sixty-three patients [median age: 63 (55–74) years; 65% men] were operated on for acute or chronic aortic dissection after previous proximal and/or distal open or endovascular thoracic aortic repair. Intraoperative details, clinical outcome and follow-up results were evaluated. RESULTS: The median time between the index and the FET procedure was 81 (40–113) months. Fifty-eight (92%) patients had already undergone proximal aortic surgery; supracoronary ascending aortic replacement was the most frequent index procedure [ n  = 25 (40%)]. Distal aortic interventions had been done in 8 (13%) patients including endovascular thoracic aortic repair in 6 patients (10%). In-hospital mortality was 3% ( n  = 2). Postoperative strokes occurred in 5 patients (8%); of those, 1 stroke was dissection-related (2%). Subsequent aortic reinterventions after the FET procedure had to be done in 33% ( n  = 21). CONCLUSIONS: Outcomes of aortic arch replacement using the FET technique after previous proximal and/or distal open or endovascular thoracic aortic repair are associated with low mortality and morbidity. Still, postoperative stroke remains an issue. After the successful accomplishments, the approach serves as an ideal platform for the secondary surgical or endovascular downstream aortic procedures, which are frequently needed.